Behind the curtain : making music in Mumbai's film studios - Booth, Gregory D. (Oxford University Press, 2008)
Introduction - Who is Anthony Gonsalves?. Part One - History, Technology, and a Determinist Milieu for Hindi Film Song. 1. Popular Music as Film Music. 3. Changing Structures in the Mumbai Film Industry. Part Two - The Life of Music in the Mumbai Film Industry. 4. Origins, Training, and "Joining the Line". 5. Roles, Relations, and the Creative Process. 6. Rehearsals, Recordings, and Economics. Part Three - Music, Instruments, and Meaning from Musicians' Perspectives. 7. Orchestras and Orchestral Procedures, Instrumental Change, Arranging, and Programming. 8. Issues of Style, Genre, a.